Towards environmental sustainability: multi-pathway exposure and health risk assessment of urban groundwater PTEs using the HHRISK code and indexical computing. - Egbueri, Johnbosco C.; Agbasi, Johnson C.; AlSaleh, Samirah Saad; Abba, Sani I.; Aralu, Chiedozie C.; Khan, Mohd Yawar Ali; Arunachalam, Krishna Prakash; Usman, Abdullahi G. (International Journal of Environmental Health Research, 2026)
Urban groundwater contamination poses significant challenges to environmental sustainability and public health, yet comprehensive risk assessments using advanced computational methods remain limited in African contexts. This research addresses this gap by integrating the Pollution Index for Groundwater (PIG) and the novel Human Health Risk (HHRISK) code to evaluate multi-pathway exposure risks from potentially toxic elements (PTEs) in Onitsha, Nigeria. Results show that 87.5% of samples were severely contaminated, primarily driven by alarming exceedances of Pb (4000% above World Health Organization guidelines), Cd (2570% above), and Ni (471% above). HHRISK analysis revealed significant health risks, with mean cumulative non-carcinogenic Hazard Index (HI) values of 16.3 (children) and 9.7 (adults), and carcinogenic risks averaging 2.1E–02 (children) and 1.1E–03 (adults); both orders of magnitude exceeding the acceptable thresholds. Regional comparisons indicated that risk magnitude scales directly with industrial intensity and anthropogenic inputs, contradicting progress toward Sustainable Development Goals (SDGs) 3 (Good Health and Well-being) and 6 (Clean Water and Sanitation) while challenging SDG 11 (Sustainable Cities and Communities) principles. The disproportionate impact on children highlights environmental justice concerns. This study advances scientific understanding of environmental chemistry and provides a basis for urban water management in rapidly urbanizing regions. Urgent remediation strategies and policies are proposed to safeguard public health and ensure critical environmental sustainability.